Польські католики в дискусії про ЄС - Крамар, Р. (Народна творчість та етнографія, 2005)
The voice of the church was very important in the Polish Referendum of 2003. They decided to say yes to the European Union and European future of the country. (95 % of Polish population consider themselves to be a strong Catholics and even if church officially did not agitate the population they had a strong influence on mass opinion. Some resolutions of the EU negatively influenced the opinion of the religious Catholics (like legalisation of abortions, homosexuality) and church insistent on the active propaganda among population of all the information (negative and positive coming from the EU). The church also was an initiator of discussions about the European way of development and national conciseness of Polls. They tried to help people to overcome their fears and to understand European way of development. With the strong attitude of Joann II his positive attitude towards European integration Polish people made their pro-Europe choice. In Ukraine this experience might not work during the national preparation for integration with Europe. first of all because of the disagreements within the Church itself and the location of main religious leadership being in located in Moscow. But there are no question that soon Ukraine will face the same set of questions about the pluses and negatives of European integration.